Стратегія розвитку екологічного інвестування в Україні - Музиченко-Козловська, О. В.; Muzychenko-Kozlovska, O. V. (Видавництво Львівської політехніки, 2023)
З’ясовано сутність поняття “стратегія”, а саме: стратегія – це послідовність дій і рішень, які здійснює організатор процесу, які ведуть до розроблення специфічної стратегії (наприклад, розвитку), призначених для того, щоб допомогти йому досягти своїх цілей та місії. Запропоновано визначення екологічних (“зелених”) інвестицій. Розроблено перелік заходів цільової програми розвитку екологічного інвестування в країні, які можуть передбачати залучення капітальних вкладень на усіх стадіях виробництва продукції.

The article clarifies the essence of the concept of “strategy”, namely: strategy is a sequence of actions and decisions taken by the organizer of the process, which lead to the development of a specific strategy (for example, development) designed to help achieve its goals and mission. The definition of ecological (“green”) investments is proposed, which includes all types of property and intellectual values that are invested in: informational, organizational, practical, commercial, marketing and economic measures that relate to the harmonization of human relations and the natural environment; environmentally friendly production and consumption; research works on the development of environmentally friendly equipment and technologies; environmental protection measures (prevention, limitation and control of harmful emissions and discharges, elimination of pollution and restoration of the environment); projects of efficient energy consumption; development of renewable energy sources; climate change management; waste management; optimal use and economic involvement of natural resources in economic activities and as a result of which profit (income) is generated and/or social and environmental effects are achieved. To achieve the goal, the research methodology used in this article includes the following stages: information provision of the strategy for the development of ecological investment in the country; establishing the mission and goals of the strategy for the development of ecological investment in the country; diagnosing the potential of investment and innovation activities in the country; forecasting the conditions of environmental investment in the country, which involves the identification of opportunities and threats; development of a strategy for the development of ecological investment in the country; evaluation of the chosen strategy; formation of a target program for the development of ecological investment in the country. A list of measures of the target program for the development of ecological investment in the country has been developed, which may involve attracting capital investments at all stages of production.
Strategy for the development of environmental investments in Ukraine
Keywords: стратегія; екологічне інвестування; “зелені” інновації; потенціал; SWOT-аналіз; природні ресурси; країна; strategy; environmental investment; “green” innovations; potential; SWOT analysis; natural resources; country; 330.332 JELR 58